High-dispersity ferric pyrophosphate colloid composite particle as well as preparation method and application thereof

By using colloidal particles as stabilizers in food processing and homogeneous emulsification technology to prepare highly dispersible iron pyrophosphate colloidal composite particles, the problems of poor dispersion and poor oxidation stability of iron pyrophosphate enhancer are solved, and better application effects are achieved.

CN119745063APending Publication Date: 2025-04-04HENAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411999504.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Iron pyrophosphate enhancer has poor dispersion and poor oxidation stability during food processing, resulting in difficulty in application.

Method used

Colloidal particles are used as stabilizers to prepare highly dispersible iron pyrophosphate colloidal composite particles through homogeneous emulsification technology to enhance their stability at the solid-liquid interface.

Benefits of technology

It significantly improves the water dispersion and oxidation stability of iron pyrophosphate, and enhances its application ability in food systems such as high protein and high oil and fat.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119745063A_ABST
    Figure CN119745063A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nutrient supplements, and provides high-dispersity ferric pyrophosphate colloid composite particles as well as a preparation method and application thereof. Colloidal particles are used as a stabilizer, and the ferric pyrophosphate colloidal composite particles are obtained by mixing ferric pyrophosphate suspension liquid and colloidal particle aqueous dispersion liquid and homogenizing and emulsifying the ferric pyrophosphate suspension liquid and the colloidal particle aqueous dispersion liquid. The ferric pyrophosphate colloidal composite particles prepared by the method have physical and chemical stability and high dispersity, and the application performance of ferric pyrophosphate in a fortified food system is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nutritional enhancers, and in particular to a highly dispersible ferric pyrophosphate colloidal composite particle and a preparation method and application thereof. Background Art

[0002] As an important raw material for nutritious and healthy food, iron nutritional fortifiers have received special attention and support. Ferric pyrophosphate is widely used as an iron nutritional fortifier in infant and young children's complementary foods due to its advantages such as lighter color, less obvious iron smell and low price. However, ferric pyrophosphate has poor water dispersibility and is prone to oxidation in fortified food systems with high oil and high protein content, which is a bottleneck problem faced in the actual application of ferric pyrophosphate.

[0003] Reducing the particle size is the most direct way to improve the water dispersibility of ferric pyrophosphate. However, due to the decrease in bulk density and the increase in specific surface energy, the surface of ultrafine ferric pyrophosphate particles is prone to electrostatic adsorption, which in turn easily leads to agglomeration. At the same time, the high-energy surface will accelerate the change of the nutritional properties of fortified foods under the influence of environmental factors such as ultraviolet radiation, high humidity, and temperature changes, making it difficult to store and eat them later. Modifying the surface of ultrafine ferric pyrophosphate particles with amphiphilic biomolecules to prepare microencapsulated ferric pyrophosphate is another technical measure to improve dispersibility. It is worth noting that the weak interaction between amphiphilic biomolecules is the main driving force for the formation of microencapsulated ferric pyrophosphate. Therefore, the poor stability of the microcapsule structure greatly affects its actual application effect as an iron fortifier.

[0004] In the early 20th century, Pickering confirmed that water-insoluble colloidal particles can replace surfactants and adsorb on the oil / water interface to stabilize emulsions (liquid-liquid heterogeneous systems). Whether colloidal particles can be used to stabilize ultrafine ferric pyrophosphate particles (solid-liquid interface) and prepare water-dispersible ferric pyrophosphate enhancers is still unknown. The stability of the prepared highly dispersible ferric pyrophosphate during food processing is even more difficult to predict.

[0005] Therefore, there is an urgent need to provide a highly dispersible ferric pyrophosphate colloidal composite particle and a preparation method and application thereof, so as to solve the bottleneck problem of ferric pyrophosphate enhancer in practical application. Summary of the invention

[0006] In view of this, the present invention provides a highly dispersible ferric pyrophosphate colloidal composite particle and a preparation method and application thereof, so as to solve the problems of poor dispersibility and poor oxidation stability of existing ferric pyrophosphate fortifiers during food processing.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The present invention provides a method for preparing highly dispersible ferric pyrophosphate colloidal composite particles, comprising the following steps:

[0009] The ferric pyrophosphate suspension is mixed with the colloidal particle aqueous dispersion and homogenized and emulsified to obtain highly dispersible ferric pyrophosphate colloidal composite particles.

[0010] Preferably, the mass concentration of the ferric pyrophosphate suspension is 4.0-12.0 mg / mL.

[0011] Preferably, the mass concentration of the colloidal particle aqueous dispersion is 3.0 to 12.0 mg / mL.

[0012] Preferably, the volume ratio of the ferric pyrophosphate suspension to the colloidal particle aqueous dispersion is 1:1-5.

[0013] Preferably, the homogenization emulsification includes low-energy rotor-stator homogenization emulsification and / or high-energy ultrasonic homogenization emulsification.

[0014] Preferably, the rotation speed of the low-energy rotor-stator homogenization emulsification is 8000-20000 rpm, and the time is 2-20 min; the power of the high-energy ultrasonic homogenization emulsification is 100-300 W, and the time is 10-30 min.

[0015] Preferably, the colloidal particles in the colloidal particle aqueous dispersion include biomacromolecule-based colloidal particles and / or polymer-based colloidal particles.

[0016] Preferably, the biomacromolecule-based colloidal particles include one or more of chitosan nanoparticles, peanut protein nanoparticles and liposomes; the polymer-based colloidal particles include one or both of polylactic acid-glycolic acid copolymer nanoparticles and polylactic acid nanoparticles.

[0017] The present invention also provides highly dispersible ferric pyrophosphate colloidal composite particles prepared by the method for preparing the highly dispersible ferric pyrophosphate colloidal composite particles.

[0018] The present invention also provides an application of the highly dispersible ferric pyrophosphate colloidal composite particles in a nutrition package.

[0019] The present invention is based on the Pickering emulsion and activation energy theory, and finds that the energy required for colloidal particles to detach from the oil-water interface is much greater than the energy of the thermal motion of the colloidal particles themselves, that is, once the micro-nanoscale colloidal particles are adsorbed to the two-phase interface (liquid-liquid interface), they can be regarded as irreversible adsorption, which is reflected in excellent stability. Based on this, the present invention creatively uses colloidal particles as stabilizers (stabilizing the solid-liquid interface) to prepare iron pyrophosphate colloidal composite particles with both high dispersibility and oxidative stability.

[0020] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention uses colloidal particles as stabilizers and adopts a homogenous emulsification method to prepare highly dispersible ferric pyrophosphate colloidal composite particles; the present invention also determines that the colloidal particles stabilize the ferric pyrophosphate mainly in the form of interface adsorption and gel formation in the system.

[0022] 2. Compared with the existing ferric pyrophosphate fortifier, the ferric pyrophosphate colloidal composite particles in the present invention are used in nutrition packages, which can significantly improve the sensory quality and oxidative stability of the nutrition packages, and are conducive to expanding the application of highly dispersible ferric pyrophosphate colloidal composite particles in easily oxidized food systems such as high-protein and high-fat foods. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0024] Figure 1 This is a dispersion concentration diagram of highly dispersible iron pyrophosphate colloidal composite particles based on chitosan nanoparticles, peanut protein nanoparticles, liposomes and PLGA nanoparticles prepared in Example 1 in water;

[0025] Figure 2 This is a transmission electron microscopy image of the iron pyrophosphate nanoparticles prepared in Example 1;

[0026] Figure 3 This is a graph showing the dispersion concentration of five groups of highly dispersible iron pyrophosphate colloidal composite particles with different chitosan concentrations prepared in Example 2 in water;

[0027] Figure 4 Graph showing the dispersion concentration of five groups of highly dispersible iron pyrophosphate colloidal composite particles in water with different ultrasonic powers prepared in Example 3;

[0028] Figure 5 Graph showing the dispersion concentration of five groups of highly dispersible iron pyrophosphate colloidal composite particles in water with different ultrasonic times prepared in Example 4;

[0029] Figure 6 This is a Fourier transform infrared spectrum of the highly dispersible ferric pyrophosphate colloidal composite particles prepared in Example 5;

[0030] Figure 7 This is a microscopic transmission electron microscope image of the highly dispersible ferric pyrophosphate colloidal composite particles prepared in Example 5;

[0031] Figure 8 This is a sensory test evaluation diagram of the highly dispersible ferric pyrophosphate colloidal composite particles prepared in Example 5 and other common iron preparations used in nutrition packs;

[0032] Fig. 9 This is the principal component analysis diagram of the total relative content of various volatile substances in the four nutrient package formulas before and after oxidation in Experimental Example 2. DETAILED DESCRIPTION

[0033] The invention provides a method for preparing highly dispersible ferric pyrophosphate colloidal composite particles, comprising the following steps: mixing a ferric pyrophosphate suspension with a colloidal particle aqueous dispersion, and performing homogenization and emulsification to obtain highly dispersible ferric pyrophosphate colloidal composite particles.

[0034] In the present invention, the mass concentration of the ferric pyrophosphate suspension is 4.0 to 12.0 mg / mL, preferably 5.0 to 10.5 mg / mL, more preferably 6.0 to 9.0 mg / mL, and more preferably 7.5 to 8.5 mg / mL.

[0035] In the present invention, the mass concentration of the colloidal particle aqueous dispersion is 3.0 to 12.0 mg / mL, preferably 5.0 to 10.0 mg / mL, more preferably 6.0 to 8.0 mg / mL, and even more preferably 7.0 mg / mL.

[0036] In the present invention, the volume ratio of the ferric pyrophosphate suspension to the colloidal particle aqueous dispersion is 1:1-5, more preferably 1:4.

[0037] In the present invention, the ferric pyrophosphate in the ferric pyrophosphate suspension is prepared by reacting an iron salt with a pyrophosphate or is commercially available.

[0038] In the present invention, the method for preparing ferric pyrophosphate preferably comprises the following steps: adding ferrous chloride dropwise to a sodium pyrophosphate aqueous solution, continuing stirring at room temperature to obtain ferric pyrophosphate, and preparing a suspension of ferric pyrophosphate particles.

[0039] In the present invention, the molar mass ratio of ferrous chloride to sodium pyrophosphate is preferably 1.2 to 1.4, more preferably 1.25 to 1.35, and more preferably 1.3; the dripping rate is preferably 40 to 500 μL / min, more preferably 70 to 300 μL / min, and more preferably 100 to 200 μL / min; the stirring speed is preferably 200 to 1000 rpm, more preferably 300 to 850 rpm, and more preferably 450 to 600 rpm; the stirring time is preferably 2 to 8 hours, more preferably 3 to 6 hours, and more preferably 5 hours.

[0040] In the present invention, the preparation method of the colloidal particle aqueous dispersion preferably includes an ion gel method, a pH driven method and a thin film dispersion method.

[0041] In the present invention, the preparation method of the colloidal particle aqueous dispersion preferably adopts an ion gel method, which comprises the following steps: adding colloidal particles into water and stirring to obtain a colloidal particle aqueous dispersion.

[0042] In the present invention, the stirring speed when preparing the colloidal particle aqueous dispersion is preferably 500-1000 rpm, more preferably 600-900 rpm, more preferably 700-800 rpm; the stirring time is preferably 0.5-2 hours, more preferably 0.8-1.5 hours, more preferably 1 hour.

[0043] In the present invention, the homogenization emulsification preferably includes low-energy rotor-stator homogenization emulsification and / or high-energy ultrasonic homogenization emulsification.

[0044] In the present invention, the rotation speed of the low-energy rotor-stator homogenization emulsification is 8000-20000rpm, preferably 8500-15000rpm, further preferably 9000-10000rpm, and more preferably 9500rpm; the time of the low-energy rotor-stator homogenization emulsification is 2-20min, and more preferably 5min; the power of the high-energy ultrasonic homogenization emulsification is preferably 100-300W, further preferably 150-320W, and more preferably 250W; the time of the high-energy ultrasonic homogenization emulsification is preferably 10-30min, further preferably 15-25min, and more preferably 20min.

[0045] In the present invention, the colloidal particles in the colloidal particle aqueous dispersion preferably include biomacromolecule-based colloidal particles and / or polymer-based colloidal particles.

[0046] In the present invention, the biomacromolecule-based colloidal particles preferably include one or more of chitosan nanoparticles, peanut protein nanoparticles and liposomes; the polymer-based colloidal particles preferably include one or two of polylactic acid-glycolic acid copolymer nanoparticles (PLGA) and polylactic acid nanoparticles.

[0047] The present invention also provides highly dispersible ferric pyrophosphate colloidal composite particles prepared by the method for preparing the highly dispersible ferric pyrophosphate colloidal composite particles.

[0048] The present invention also provides an application of the highly dispersible ferric pyrophosphate colloidal composite particles in a nutrition package.

[0049] In the present invention, the application of the highly dispersible ferric pyrophosphate colloidal composite particles in a nutrient pack refers to adding the highly dispersible ferric pyrophosphate colloidal composite particles into the nutrient pack.

[0050] In the present invention, before adding the highly dispersible ferric pyrophosphate colloidal composite particles into the nutrient pack, the method further includes processing the highly dispersible ferric pyrophosphate colloidal composite particles to obtain highly dispersible ferric pyrophosphate colloidal composite powder.

[0051] In the present invention, the processing operations preferably include spray drying, freeze drying and hot air drying.

[0052] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0053] Example 1

[0054] (1) Add ferrous chloride to a sodium pyrophosphate aqueous solution at a drop rate of 100 μL / min, and ensure that the molar mass ratio of ferrous chloride to the sodium pyrophosphate aqueous solution is 4:3. After the dropwise addition is completed, continue stirring at a rotation speed of 1000 rpm for 2 hours to obtain ferric pyrophosphate, and prepare a ferric pyrophosphate particle suspension with a mass concentration of 6 mg / mL.

[0055] (2) 60 mg of chitosan nanoparticles, peanut protein nanoparticles, liposomes and polylactic acid-co-glycolic acid nanoparticles (PLGA) were dispersed in 10 mL of deionized water respectively, and stirred at 1000 rpm for 1 hour to obtain chitosan nanoparticle aqueous dispersion, peanut protein nanoparticle aqueous dispersion, liposome aqueous dispersion and PLGA aqueous dispersion with a mass concentration of 6 mg / mL.

[0056] (3) 10 mL of the ferric pyrophosphate particle suspension was added to 40 mL of chitosan nanoparticle aqueous dispersion, peanut protein nanoparticle aqueous dispersion, liposome aqueous dispersion and PLGA aqueous dispersion, respectively, and then high-energy ultrasonic homogenization and emulsification were performed at a power of 200 W for 20 min to obtain highly dispersible ferric pyrophosphate colloidal composite particles based on chitosan, peanut protein, liposome and PLGA.

[0057] The iron pyrophosphate colloidal composite particles obtained in Example 1 were respectively recorded as chitosan, peanut protein, liposome and PLGA groups, and iron pyrophosphate without colloidal particles was added (recorded as control) to determine the stable dispersion concentration of iron pyrophosphate in water by inductively coupled plasma mass spectrometry. The results are as follows Figure 1 As shown, from Figure 1It can be seen that the stable dispersion concentrations of high-dispersibility ferric pyrophosphate colloidal composite particles obtained by homogenizing and emulsifying different colloidal particles and ferric pyrophosphate particle suspensions are different. Compared with ferric pyrophosphate without adding colloidal particles, the high-dispersibility ferric pyrophosphate colloidal composite particles added with colloidal particles in the present invention have a better stable dispersion concentration in water; among them, the high-dispersibility ferric pyrophosphate colloidal composite particles prepared using chitosan nanoparticles have the best stable dispersion concentration in water, which can significantly improve the dispersibility of ferric pyrophosphate.

[0058] The highly dispersible ferric pyrophosphate colloidal composite particles prepared in Example 1 were characterized by transmission electron microscopy. Figure 2 As shown by Figure 2 From the scanning electron microscope image, we can see that although the particle size of the iron pyrophosphate nanoparticles is as low as 50nm, they are still easy to aggregate. The possible reason is that the surface energy of iron pyrophosphate with small particle size is higher and it is easy to aggregate.

[0059] Example 2

[0060] (1) Add ferrous chloride to a sodium pyrophosphate aqueous solution at a drop rate of 50 μL / min, and ensure that the molar mass ratio of ferrous chloride to the sodium pyrophosphate aqueous solution is 4:3. After the dropwise addition is completed, continue stirring at a rotation speed of 1000 rpm for 2 hours to obtain ferric pyrophosphate, and prepare a ferric pyrophosphate particle suspension with a mass concentration of 6 mg / mL.

[0061] (2) 20, 40, 60, 80, and 100 mg of chitosan nanoparticles were dispersed in 10 mL of deionized water, respectively, and stirred at 1000 rpm for 1 hour to obtain five groups of colloidal particle aqueous dispersions with mass concentrations of 2, 3, 4, 5, and 6 mg / mL, respectively.

[0062] (3) 10 mL of the ferric pyrophosphate particle suspension was added to the five groups of colloidal particle aqueous dispersions obtained in step (2), with each group of colloidal particle aqueous dispersions being 40 mL. First, rotor-stator homogenization and emulsification were performed at a speed of 20,000 rpm for 5 min, and then ultrasonic homogenization and emulsification were performed at a power of 200 W for 20 min to obtain five groups of highly dispersible ferric pyrophosphate colloidal composite particles with different chitosan concentrations.

[0063] The concentrations of the five groups of chitosan stabilizers in Example 2 were 2, 3, 4, 5, and 6 mg / mL, respectively. The stable dispersion concentration of ferric pyrophosphate in water was determined by inductively coupled plasma mass spectrometry. The results are as follows: Figure 3As shown in the figure, the change of chitosan concentration will affect the stable dispersion concentration of ferric pyrophosphate in water. When the concentration of chitosan aqueous dispersion is 2 mg / mL, the stable dispersion concentration of ferric pyrophosphate in water is the worst. When the concentration of chitosan aqueous dispersion is 3-6 mg / mL, the dispersion stability is better. When the concentration of chitosan aqueous dispersion is 3 mg / mL, the stable dispersion concentration of ferric pyrophosphate in water is the best, reaching 1.73 mg / mL, indicating that when the concentration of chitosan aqueous dispersion is 3 mg / mL, the ability of chitosan colloidal particles to stabilize ferric pyrophosphate is the strongest.

[0064] Example 3

[0065] (1) Add ferrous chloride to a sodium pyrophosphate aqueous solution at a drop rate of 100 μL / min, and ensure that the molar mass ratio of ferrous chloride to the sodium pyrophosphate aqueous solution is 4:3. After the dropwise addition is completed, continue stirring at a rotation speed of 1000 rpm for 2 hours to obtain ferric pyrophosphate, and prepare a ferric pyrophosphate particle suspension with a mass concentration of 6 mg / mL.

[0066] (2) Disperse five portions of 40 mg chitosan nanoparticles in 10 mL of deionized water and stir at 1000 rpm for 1 hour to obtain five groups of colloidal particle aqueous dispersions with a mass concentration of 4 mg / mL.

[0067] (3) Five portions of 10 mL of the pyrophosphate iron particle suspension were added to the five groups of colloidal particle aqueous dispersions obtained in step (2), each group of colloidal particle aqueous dispersions being 40 mL. First, rotor-stator homogenization and emulsification were performed at a rotation speed of 20,000 rpm for 5 min. Then, high-energy ultrasonic homogenization and emulsification were used to ultrasonically emulsify the five groups of mixed solutions at ultrasonic powers of 100, 150, 200, 250, and 300 W for 20 min, respectively, to obtain five groups of highly dispersible pyrophosphate iron colloidal composite particles with different ultrasonic powers.

[0068] The five groups of highly dispersible ferric pyrophosphate colloidal composite particles prepared in Example 3 with different ultrasonic powers were measured for the stable dispersion concentration of ferric pyrophosphate in water by inductively coupled plasma mass spectrometry. The results are as follows: Figure 4 As shown, from Figure 4 It can be seen that when the ultrasonic power is in the range of 100-250W, the stable dispersion concentration of ferric pyrophosphate in water increases with the increase of ultrasonic power, and when the ultrasonic power is 250W, the stable dispersion concentration of ferric pyrophosphate in water is the highest, reaching 1.73mg / mL, but when the ultrasonic power exceeds 250W, the water dispersion concentration of ferric pyrophosphate will gradually decrease.

[0069] Example 4

[0070] (1) Add ferrous chloride to a sodium pyrophosphate aqueous solution at a drop rate of 150 μL / min, and ensure that the molar mass ratio of ferrous chloride to the sodium pyrophosphate aqueous solution is 4:3. After the dropwise addition is completed, continue stirring at a rotation speed of 1000 rpm for 2 hours to obtain ferric pyrophosphate, and prepare a ferric pyrophosphate particle suspension with a mass concentration of 6 mg / mL.

[0071] (2) Disperse five portions of 60 mg chitosan nanoparticles in 10 mL of deionized water and stir at 1000 rpm for 1 hour to obtain five groups of colloidal particle aqueous dispersions with a mass concentration of 6 mg / mL.

[0072] (3) Five portions of 10 mL of the pyrophosphate iron particle suspension were added to five groups of colloidal particle aqueous dispersions obtained in step (2), each group of colloidal particle aqueous dispersions being 40 mL. First, rotor-stator homogenization emulsification was performed at a rotation speed of 20,000 rpm for 5 min. Then, high-energy ultrasonic homogenization emulsification was used to ultrasonically emulsify the five groups of mixed solutions at an ultrasonic power of 250 W for 10, 15, 20, 25, and 30 min, respectively, to obtain five groups of highly dispersible pyrophosphate iron colloidal composite particles with different ultrasonic times.

[0073] The five groups of highly dispersible ferric pyrophosphate colloidal composite particles prepared in Example 4 with different ultrasonic times were measured for the stable dispersion concentration of ferric pyrophosphate in water by inductively coupled plasma mass spectrometry. The results are as follows: Figure 5 As shown, from Figure 5 It can be seen that when the ultrasonic time is 20 min, the stable dispersion concentration of ferric pyrophosphate in water is the highest, reaching 1.73 mg / mL, indicating that the ability of chitosan colloidal particles to stabilize ferric pyrophosphate is strongest when the ultrasonic time is 20 min.

[0074] Example 5

[0075] (1) Add ferrous chloride to a sodium pyrophosphate aqueous solution at a drop rate of 200 μL / min, and ensure that the molar mass ratio of ferrous chloride to the sodium pyrophosphate aqueous solution is 4:3. After the dropwise addition is completed, continue stirring at a rotation speed of 1000 rpm for 2 hours to obtain ferric pyrophosphate, and prepare a ferric pyrophosphate particle suspension with a mass concentration of 6 mg / mL.

[0076] (2) 60 mg of chitosan nanoparticles were dispersed in 10 mL of deionized water and stirred at 1000 rpm for 1 hour to obtain a colloidal particle aqueous dispersion with a mass concentration of 6 mg / mL.

[0077] (3) 10 mL of the pyrophosphate iron particle suspension was added to 40 mL of the colloidal particle aqueous dispersion obtained in step (2). First, rotor-stator homogenization emulsification was performed at a rotation speed of 20,000 rpm for 5 min. Then, high-energy ultrasonic homogenization emulsification was performed at an ultrasonic power of 250 W for 20 min to obtain highly dispersible pyrophosphate iron colloidal composite particles.

[0078] The microstructure and intermolecular interactions of the highly dispersible ferric pyrophosphate colloidal composite particles (highly dispersible ferric pyrophosphate) prepared in Example 5 were characterized by Fourier transform infrared spectroscopy and transmission electron microscopy. The results are as follows: Figures 6-7 As shown, from Figure 6 It can be seen from the Fourier transform infrared spectrum that chitosan nanoparticles are soluble nanoparticles prepared by chitosan and sodium tripolyphosphate. In the chitosan / sodium tripolyphosphate system, when using a rapid mixing method at a low charge ratio, chitosan and sodium tripolyphosphate can form a soluble complex under the condition of uniform mixing. Under the condition of rapid and uniform mixing, the complexation of polyelectrolytes should conform to the complexation mechanism of "uniform distribution". Figure 6 It can also be seen from the Fourier transform infrared spectrum that the high-dispersibility ferric pyrophosphate has -1 There are absorption peaks at all locations, indicating that the complex contains chitosan, sodium tripolyphosphate and ferric pyrophosphate, the amino groups of chitosan interact with phosphate esters, and the hydroxyl groups of chitosan bind to iron ions. Figure 7 It can be seen from the microscopic transmission electron micrograph that the ferric pyrophosphate based on the particle stabilizer has good dispersion under microscopic conditions. Figure 2 The transmission electron microscopy image in the figure is better than that in the figure, indicating that chitosan nanoparticles can improve the dispersion of ferric pyrophosphate; Figure 7 It can also be observed that the colloidal particles stabilize ferric pyrophosphate mainly in the form of interfacial adsorption and gel formation in the system. Therefore, the interfacial adsorption and gelation of the colloidal particles are two decisive factors for improving the dispersibility of ferric pyrophosphate.

[0079] Example 6

[0080] (1) adding ferrous chloride to a sodium pyrophosphate aqueous solution at a dropping rate of 200 μL / min, and ensuring that the molar mass ratio of ferrous chloride to the sodium pyrophosphate aqueous solution is 1.2, and continuing to stir at a rotation speed of 850 rpm for 3 hours after the dropping is completed to obtain ferric pyrophosphate, and preparing a ferric pyrophosphate particle suspension with a mass concentration of 8 mg / mL.

[0081] (2) 60 mg of chitosan nanoparticles were dispersed in 10 mL of deionized water and stirred at 800 rpm for 1.5 hours to obtain a colloidal particle aqueous dispersion with a mass concentration of 6 mg / mL.

[0082] (3) 10 mL of the pyrophosphate iron particle suspension was added to 10 mL of the colloidal particle aqueous dispersion obtained in step (2). First, rotor-stator homogenization emulsification was performed at a rotation speed of 20,000 rpm for 2 min. Then, high-energy ultrasonic homogenization emulsification was performed at an ultrasonic power of 100 W for 30 min to obtain highly dispersible pyrophosphate iron colloidal composite particles.

[0083] Example 7

[0084] (1) adding ferrous chloride to a sodium pyrophosphate aqueous solution at a dropping rate of 200 μL / min, and ensuring that the molar mass ratio of ferrous chloride to the sodium pyrophosphate aqueous solution is 1.4, and continuing to stir at a rotation speed of 450 rpm for 5 hours after the dropping is completed to obtain ferric pyrophosphate, and preparing a ferric pyrophosphate particle suspension with a mass concentration of 4 mg / mL.

[0085] (2) 60 mg of chitosan nanoparticles were dispersed in 10 mL of deionized water and stirred at 500 rpm for 2 hours to obtain a colloidal particle aqueous dispersion with a mass concentration of 6 mg / mL.

[0086] (3) 10 mL of the pyrophosphate iron particle suspension was added to 50 mL of the colloidal particle aqueous dispersion obtained in step (2). First, rotor-stator homogenization emulsification was performed at a rotation speed of 20,000 rpm for 20 min. Then, high-energy ultrasonic homogenization emulsification was performed at an ultrasonic power of 300 W for 10 min to obtain highly dispersible pyrophosphate iron colloidal composite particles.

[0087] Application Example 1 Preparation of Nutrition Pack

[0088] The highly dispersible ferric pyrophosphate colloidal composite particles prepared in Example 5 were processed by spray drying to obtain highly dispersible ferric pyrophosphate colloidal composite powder; and then the highly dispersible ferric pyrophosphate colloidal composite powder was used as an iron fortifier to prepare a nutrient pack.

[0089] The formula and preparation method of the nutrient pack are as follows: 25 g of Class I instant soybean powder, 35 g of maltodextrin, 8 g of instant egg yolk powder, 15 g of whole milk powder, 5 g of glucose whole sugar powder, 2250 mg of L-calcium lactate, 60 mg of zinc citrate, 1.2 mg of vitamin A acetate, 30 μg of thiamine hydrochloride, 0.6 mg of riboflavin, 1 mg of pyridoxine hydrochloride, 0.05 mg of cyanocobalamin, 0.5 g of ascorbic acid and an iron fortifier are mixed to obtain a nutrient pack.

[0090] According to the formula and preparation method of the above-mentioned nutrient package, the following four samples were prepared: Sample 1 used ferrous sulfate as an iron fortifier, with an addition amount of 0.15g; Sample 2 used ferric pyrophosphate as an iron fortifier, with an addition amount of 0.176g; Sample 3 used the highly dispersible ferric pyrophosphate colloidal composite particles prepared in Example 5 as an iron fortifier, with an addition amount of 0.235g; Sample 4 did not add an iron fortifier (control group). Among them, the ferric pyrophosphate in Sample 2 was the ferric pyrophosphate powder obtained by spray drying the ferric pyrophosphate particle suspension prepared in step (1) of Example 5.

[0091] Experimental Example 1

[0092] The four nutrient packs prepared in Example 1 were subjected to accelerated oxidation experiments. The accelerated oxidation conditions were 40°C constant temperature accelerated for 28 days to evaluate the effects of different iron fortifiers on the storage stability of the nutrient packs. The results are shown in Tables 1 and Figure 8 shown.

[0093] Table 1 Sensory evaluation of nutrient packs during accelerated storage

[0094]

[0095] It can be seen from Table 1 that the highly dispersible iron pyrophosphate nutrient pack prepared by the highly dispersible iron pyrophosphate colloidal composite particles of the present invention only showed a slight rancid smell in the third week, which indicates that the nutrient pack prepared by the highly dispersible iron pyrophosphate colloidal composite particles of the present invention has better antioxidant and stability performance than the ordinary iron pyrophosphate nutrient pack.

[0096] Depend on Figure 8 It can be seen that sample 1 developed a rancid smell on the 14th day, sample 2 developed a rancid smell on the 7th day, and sample 3 and sample 4 developed a rancid smell on the 21st day. Among them, the rancid smells of samples 1 and 2 were heavier, while sample 3 had a moderate rancid smell and sample 4 had a lighter rancid smell.

[0097] Experimental Example 2

[0098] Solid phase microextraction (GC-MS) was used to determine the oxide content of the four nutrient packs prepared in Example 1. The four nutrient pack formulas were fitted into a model using SIMCA13.0 software, and the principal component analysis was performed on the total relative content of various volatile substances before and after oxidation. The results are as follows: Fig. 9 As shown, from Fig. 9 It can be seen that the odd-numbered marks are unoxidized, and the even-numbered marks are oxidized samples. Among them, the volatile characteristic substances aldehydes and ketones of the highly dispersed ferric pyrophosphate system change little, indicating that its degree of lipid oxidation is low and it has excellent antioxidant properties.

[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing highly dispersible ferric pyrophosphate colloidal composite particles, characterized in that: The steps include: The ferric pyrophosphate suspension is mixed with the colloidal particle aqueous dispersion and homogenized and emulsified to obtain highly dispersible ferric pyrophosphate colloidal composite particles.

2. The method for preparing a highly dispersible ferric pyrophosphate colloidal composite particle according to claim 1, characterized in that: The mass concentration of the ferric pyrophosphate suspension is 4.0-12.0 mg / mL.

3. The method for preparing a highly dispersible ferric pyrophosphate colloidal composite particle according to claim 2, characterized in that: The mass concentration of the colloidal particle aqueous dispersion is 3.0-12.0 mg / mL.

4. The method for preparing a highly dispersible ferric pyrophosphate colloidal composite particle according to any one of claims 1 to 3, characterized in that: The volume ratio of the ferric pyrophosphate suspension to the colloidal particle aqueous dispersion is 1:1-5.

5. The method for preparing a highly dispersible ferric pyrophosphate colloidal composite particle according to claim 4, characterized in that: The homogenization emulsification includes low-energy rotor-stator homogenization emulsification and / or high-energy ultrasonic homogenization emulsification.

6. The method for preparing a highly dispersible ferric pyrophosphate colloidal composite particle according to claim 5, characterized in that: The rotation speed of the low-energy rotor-stator homogenization emulsification is 8000-20000 rpm, and the time is 2-20 minutes; The power of the high-energy ultrasonic homogenization emulsification is 100-300W, and the time is 10-30 minutes.

7. The method for preparing a highly dispersible ferric pyrophosphate colloidal composite particle according to claim 6, characterized in that: The colloidal particles in the colloidal particle aqueous dispersion include biomacromolecule-based colloidal particles and / or polymer-based colloidal particles.

8. The method for preparing a highly dispersible ferric pyrophosphate colloidal composite particle according to claim 7, characterized in that: The biomacromolecule-based colloidal particles include one or more of chitosan nanoparticles, peanut protein nanoparticles and liposomes; The polymer-based colloidal particles include one or both of polylactic acid-glycolic acid copolymer nanoparticles and polylactic acid nanoparticles.

9. Highly dispersible ferric pyrophosphate colloidal composite particles prepared by the method for preparing highly dispersible ferric pyrophosphate colloidal composite particles according to any one of claims 1 to 8.

10. Use of the highly dispersible ferric pyrophosphate colloidal composite particles according to claim 9 in a nutrition package.